The impact of special exercises in the method of circular training in the development of the skill of controlling the ball in football players category junior - recham djamal eddine (sports creativity, 2025)
The aim of this study is to try to determine the extent to which the proposed exercises contribute to the development of the skill of ball control in the football players in the junior category. On the field and methodological side, the study was conducted on the football teams who are active at the level of the State League Representing the research community. The sample was chosen in a simple random way. Our selection was signed by two clubs: (WOB) and (UBM) The experimental method was used in the study using the ball control skill as a tool for collecting the data after subjecting it to the scientific conditions. On the statistical side, the statistical package was used to calculate the simple correlation coefficient Pearson R and Test T. "Studied to analyze the data obtained by the members of the research sample. After the data collection and analysis results resulted in the realization of the hypotheses that were formulated at the beginning of the study